Enhancing the accessibility of starch size and cellulose to enzymes in raw cotton woven fabric by air-plasma pretreatment. Issue 8 (May 2016) - Szabo, Orsolya Erzsebet; Csiszar, Emilia; Koczka, Bela; Toth, Andras; Klebert, Szilvia
In this paper, raw cotton fabric was pretreated with non-thermal atmospheric air-plasma and the accessibility of the surface polymers of the fibers and yarns that act as respective substrates for the enzymes was evaluated. Results proved that plasma slightly destroyed and oxidized the starch size on the surface of warp yarns and partially removed the thin and perfectly hydrophobic waxy coverage of the fibers in weft yarns, creating deep "pits" with a depth of 215 nm. This latter process contributed to the exposure of cellulose and pectin located under the waxy outer layer of the elementary fibers in the weft yarns, and significantly increased the surface roughness of the fibers (from Rq of 25 to 67 nm for the raw and 180 s plasma-treated samples, respectively). Amount of the reducing sugars released during the amylase and cellulase digestion of the plasma-treated fabrics confirmed that air-plasma significantly increased the accessibility of the starch and cellulose, respectively, to the enzymes and resulted in an enhanced solubilization of both polymers. Since the plasma-treated substrates displayed significantly faster enzyme reactions, the time of enzymatic treatments can be sharply reduced.